COMPARISON OF PATCHING DURATION ON AMBLYOPIC CHILDREN IN CMH MUZAFFARABAD - Malik, Sidra; Zaib, Iqra; Farooq, Omer; Hanif, Kanwal (Pakistan Journal of Ophthalmology, 2019)
Objective: To Compare the efficacy of 2 different patching regimens in amblyopic children and highlight the factors affecting compliance. Materials & Methods: The randomized control trial was conducted in Eye OPD SKBZ Hospital Muzaffarabad from September 2017- March 2018. Analysis was limited to children 4 to 16 years of age with unilateral amblyopia. Personal information, visual acuity with and without correction, Cycloplegic refraction & subjective refraction was noted. Children with amblyopic eye acuity of 20/40 to 20/200 (mean 0.56 log MAR, approximately 20/63) and inter ocular acuity difference of 2 or more lines were specified to get either 2 hours (Group A) or 6 hours (Group B) of daily patching, combined with 1 hour of near visual activities per day. Follow up period was 2 weeks, 4 weeks and 3 months. Results: Out of 72 children 44(61.1%) were males and 28(38.9%) were females. The mean age was 10.25 ± 0.67 years. Mean visual acuity was 20/63(+0.5 log Mar) in both groups. In group A, 66.7 % and in group B 83.3% of patients showed improvement. The mean difference of BCVA was 2.77 ± 1.28 SD and 3.41±3.16 SD in group ‘A’ and group ‘B’ respectively. Group A and B showed improvement of 3.0 and 2.0 lines respectively. Both groups showed a poor compliance of 11.2 %. Conclusion: 2 hours of patching along with 1 hour of near activity is sufficient to treat amblyopia as compared to 6 hours of patching. Firstly, screening should be done to diagnose amblyopia at early stage. Secondly compliance is found to be a single most important factor to improve outcomes.